CLINICAL EVALUATION OF COMPARATIVE AND COMBINED EFFECT OF POLYHERBAL MICROBICIDE (BASANT) AND SELECTED PROBIOTICS IN THE TREATMENT OF RECCURRENT VAGINOSIS - A PHASE II PLACEBO CONTROLLED TRIAL - Kriplani, Alka; Sehgal, Rohini; Atrey, Nishu; Singh, Priyanka; Ganguly, Indrani; Sinha, Soni; C Gupta, Jagdish; Talwar, G. P. (International Journal of Ayurveda and Pharma Research, 2015)
Background: Vaginosis is a widely prevalent syndrome in women. Treatment with one or more antibiotics cures invariably the infections. However recurrence is frequent and pH of the vagina is not always restored to the normal acidic range. This trial was conducted to determine whether a Polyherbal Microbicide BASANT or three selected strains of Probiotics Lactobacilli alone or the two in combination can regress Vaginosis, bring down the vaginal pH to acidic range and restore healthy vagina with colonised Lactobacilli. Methods: Women suffering from recurrent episodes of vaginosis were given capsules of either BASANT, Probiotics, Combination of the two or Placebo capsules for insertion in vagina for 7 nights. On day 10, Pelvic examination, pH, Whiff test, Gram stain for Clue cells and swab taken for culture of lactobacilli. Results: BASANT regressed Vaginosis in 14/ 20, Probiotics in 13/20, Combination of the two in 19/ 20 women and Placebo in 1/ 20 women. Conclusion: While both Polyherbal microbicide BASANT and the three strains of the lactobacilli cured Vaginosis in 65 to 70% of women, the combination was highly effective in curing 95% of women.